(untitled) (Experimental biology, 2017)
Etanol cultivation carbonized acid sorbent on the Rice Hush base prefer the sorbtion property in attidude Lactobacillus cells. Cells immobilization of Lactobacillus is elevate their stability to gastrict juise, and stimulate antagonistic activity.